Study on biosynthesis and recovering of S-adenosyl-L-methionine (SAM) from Saccharomyces strains - Hương Lê Thị Mai; Toàn Phạm Đức; Trọng Lê Văn; Trâm Nguyễn Thị Hoài; Hòa Hoàng Đình (Vietnam Journal of Biotechnology, 2008)
Journal of Biotechnology 3(1): 105-114, 2005